2009
DOI: 10.1167/iovs.08-2683
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar Optic Nerve Diameter Measured by High-Speed Magnetic Resonance Imaging as a Biomarker for Axonal Loss in Glaucomatous Optic Atrophy

Abstract: Retina- or optic nerve head-related surrogate markers for axonal content correlated closely with the OND, although only when it was measured in the orbital apex. High-resolution MRI using an ultrafast HASTE-sequence at 3 T proved useful for OND quantification and may be a valuable asset in future neuroprotection trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 34 publications
4
35
0
2
Order By: Relevance
“…A negative correlation between the mean FA for the optic nerves and glaucoma stage was reported [10]. According to two recent studies, -the optic nerve diameter was most closely related to the retinal nerve fiber layer thickness measured by an OCT [22,23]. In our study, optic nerve-1 diffusion parameters were found to be more closely correlated with OCT and VF findings.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A negative correlation between the mean FA for the optic nerves and glaucoma stage was reported [10]. According to two recent studies, -the optic nerve diameter was most closely related to the retinal nerve fiber layer thickness measured by an OCT [22,23]. In our study, optic nerve-1 diffusion parameters were found to be more closely correlated with OCT and VF findings.…”
Section: Discussionsupporting
confidence: 66%
“…Lagreze et al measured the diameter of retrobulbar optic nerves with an ultrafast high-resolution MRI at 3T. Included in the study were 38 glaucomatous, and nine healthy eyes [22]. Similar findings were obtained with 3T-DTI in 38 subjects [23].…”
Section: Discussionmentioning
confidence: 59%
“…In the present study, the echographic evaluation was performed with a 20 MHz highre solution probe and the procedure showed a strong correlation with C/D (BIO) measures both in terms of the C/OND (US) ratio and the direct measurement of the optic nerve cup. Previous investigations have shown that in glaucomatous patients the thickness of the retrobulbar optic nerve decreases with di sease progression, a fact that would likely lead to a better correlation with the C/OND (US) proportion (10)(11)(12) . With the evolution of the disease, an increase in the C/D ratio would be assumed to occur possibly due to the shrinking thickness of the retrobulbar optic nerve (denominator), resulting in a proportion that would vary in a more sensitive fashion than the simple C/D ratio.…”
Section: Discussionmentioning
confidence: 99%
“…(83)(84)(85)(86)(87) High-resolution magnetic resonance imaging (MRI) using an ultra fast HASTE-sequence at 3 T sequences of the optic nerve can portray axonal loss in the optic nerve comparing closely with the retinal nerve fiber layer-related parameters and could be used as a biomarker for axonal loss in glaucoma. (82) 3-T diffusion tensor imaging of the optic nerve in patients with glaucoma displays good correlation with the retinal nerve fiber layer thickness measured by OCT and may serve as a biomarker of disease severity. (88) The majority of the ganglion cells axons terminate in the lateral geniculate nucleus (LGN), the major relay station between the retina and the visual cortex.…”
Section: Neurodegenerative Markersmentioning
confidence: 97%
“…As retinal ganglion cell axons project to the central nervous system, their number within the retrobulbar optic nerve may be a suitable surrogate marker for optic atrophy. (82) Thinning of the retrobulbar optic nerve has been reported both in histological and diagnostic imaging studies suggesting that the diameter of the nerve may correlate with the extent of the optic atrophy. (83)(84)(85)(86)(87) High-resolution magnetic resonance imaging (MRI) using an ultra fast HASTE-sequence at 3 T sequences of the optic nerve can portray axonal loss in the optic nerve comparing closely with the retinal nerve fiber layer-related parameters and could be used as a biomarker for axonal loss in glaucoma.…”
Section: Neurodegenerative Markersmentioning
confidence: 99%